Hear Where We Are Sound, Ecology, and Sense of Place - Stocker, Michael (Springer New York : Imprint: Springer, 2013)
Throughout history, hearing and sound perception have been typically framed in the context of how sound conveys information and how that information influences the listener. Hear Where We Are inverts this premise and examines how humans and other hearing animals use sound to establish acoustical relationships with their surroundings. This simple inversion reveals a panoply of possibilities by which we can re-evaluate how hearing animals use, produce, and perceive sound. Nuance in vocalizations become signals of enticement or boundary setting; silence becomes a field ripe in auditory possibilities; predator/prey relationships are infused with acoustic deception, and sounds that have been considered territorial cues become the fabric of cooperative acoustical communities. This inversion also expands the context of sound perception into a larger perspective that centers on biological adaptation within acoustic habitats. Here, the rapid synchronized flight patterns of flocking birds and the tight maneuvering of schooling fish becomes an acoustic engagement. Likewise, when stridulating crickets synchronize their summer evening chirrups, it has more to do with the 'cricket community' monitoring their collective boundaries rather than individual crickets establishing 'personal' territory or breeding fitness. In Hear Where We Are the author continuously challenges many of the bio-acoustic orthodoxies, reframing the entire inquiry into sound perception and communication. By moving beyond our common assumptions, many of the mysteries of acoustical behavior become revealed, exposing a fresh and fertile panorama of acoustical experience and adaptation. Praise for Hear Where We Are: "Hear Where We Are is as poetic as it is informative - in the tradition of some of the best scientific writing." Julia Whitty, Author, Deep Blue Home: An Intimate Ecology of Our Wild Ocean "Hear Where We Are opens up an entirely new way of understanding not only sound perception but our place within the world... I no longer just hear my surroundings, rather I am now aware of how deeply sound shapes my relationship to the world around me..." Kevin W. Kelley, Author, The Home Planet                                                                                                                                                                                                          .